REVIEW OF ISLAMIC LAW ON GOAT PRODUCTION SHARING: case study in the village of Gandanglegi, Malang - adib, roisul (Ahwal Al-Syakhsiyyah Fakultas Syariah - Universitas Al-Qolam Malang, 2023)
In social life there must be such things as rules to guide. In the state, laws are used as rules and prohibitions as well as sanctions for every individual or group who violates them. In Islam, many kinds of laws are used, one of which is Islamic law regarding buying and selling, namely muamalah fiqh. In this business, you entrust pets to other people. The results of this research can be concluded that the Study of Goat Livestock Results in the Perspective of Sharia Economic Law in Ganjaran Village is a type of Syirkah Mudharabah which is carried out orally. Sharing the results of goat farming is still done according to custom, namely by the goats that are born, if one goat is born then it is sold first and then divided in half. If a goat gives birth to 2 goats, each of them gets 1 goat. The second way to share the results is by taking turns with the goat kids, the first born child goes to (mudharib) the second child goes to (shahibul mall) and so on, while for male goats the way to share the results is by selling them first, then the profits from the sale are divided into two.